MODEL AIDA PADA PELAYANAN PELANGGAN UNTUK MENINGKATKAN KEPUTUSAN PEMBELIAN - Rifki Hanif; Agus Purnomo Sidi; Afira Rahmatul Annisa (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
This study aims to evaluate the influence of the AIDA (Attention, Interest, Desire, Action) communication strategy on consumers' purchase decisions in online stores. The rapid development of the internet in Indonesia has changed the way people conduct transactions, with the emergence of various online shopping sites. The method used is descriptive quantitative with a sample of 100 consumers. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that all AIDA variables significantly influence purchase decisions, with t-values of each variable being greater than the t-table value and a significance level of less than 0.05. The conclusion of this study is that the AIDA communication strategy is effective in increasing consumers' purchase decisions in online stores. Pelayanan Pelanggan that can provide clear, engaging, and consistent information with advertisements plays a crucial role in this. The implications of these findings underscore the importance of Pelayanan Pelanggan training in communication strategies to enhance consumer purchase decision.